Does The Use of Ethyl Chloride Improve Patient-Reported Pain Scores With Negative Pressure Wound Therapy Dressing Changes? A Prospective, Randomized Controlled Trial. Issue 6 (June 2021) - Tank, Jason C.; Georgiadis, Gregory M.; Bair, Jeffrey M.; Rice, Alexi; O'Mara Gardner, Kristin; Chen, John T.; Redfern, Roberta E.
Abstract : Background: Negative pressure wound therapy (NPWT) is commonly used for surgical incisions and large wounds, particularly in the context of trauma. Research has shown that patients report that the most painful aspect of NPWT is related to foam dressing changes. This study aimed to determine whether topical use of the vapocoolant anesthetic ethyl chloride would impact patient-reported pain during these procedures. Methods: This study was a single-blinded, placebo-controlled randomized trial in patients who were undergoing NPWT foam dressing change following surgery performed by the orthopedic trauma team. A total of 100 patients were randomized to receive ethyl chloride topical anesthetic spray or placebo (tissue culture grade water) during dressing change. The outcome measure specified prior to enrollment was a mean decrease in patient-reported pain of 1.7 points using a numeric rating scale. Baseline and procedural characteristics were collected to investigate contributions to patient-reported pain. We hypothesized that the use of ethyl chloride would decrease patient reported pain scores. Results: Significantly more females were randomized to the receive vapocoolant; remaining baseline and procedural characteristics were similar between groups. The median time for NPWT drape removal was 2.0 minutes in both groups ( p = 0.66). The postprocedural pain reported by patients was significantly lower in the experimental group compared with placebo (median, 5.0 vs. 7.0; p = 0.03). Multivariate analysis adjusting for potential confounders showed treatment group to be the strongest predictor of postprocedure pain ( p = 0.002). Additionally, a generalized linear model suggests that treatment group was the strongest predictor of change in pain score as reported by patients prior to and immediately following dressing change. Conclusions: Use of vapocoolant spray during NPWT dressing change for orthopedic trauma wounds and surgical incisions was feasible and resulted in significant reduction in patient-reported pain associated with the procedure. LEVEL OF EVIDENCE: Therapeutic, Level I